Foreign and national implementation practice of the state policy of railway indusry restructuring for strengthening its competitive position - Mnykh, O.; Polovska, V.; Kholyavka, V. (Видавництво Львівської політехніки, 2016)
The generalization of the foreign and national practice of the state policy of the railway industry restructuring with identification of its key provisions was performed. The originating sources of the railway industry market position degradation issue were identified. The topical tasks of Ukrzaliznytsia PJSC on the today’s stage of its reforming for strengthening of its market position were defined. The potential opportunities and peculiarities of the public and private companies’ interaction in the rolling stock repairs and modernization process were explored. Проведено узагальнення закордонної та вітчизняної практики державної політики реструктуризації у сфері залізничного транспорту і визначено її ключові положення. Ідентифіковані джерела походження проблеми погіршення ринкових позицій галузі залізничного транспорту. Визначено актуальні задачі ПАТ “Укрзалізниця” на сучасному етапі його реформування для зміцнення його ринкових позицій. Досліджено потенційні можливості та особливості взаємодії державних та приватних підприємств під час ремонту й модернізації рухомого складу.
Міжнародна і національна практика імплементації державної політики реструктуризації залізничної галузі з метою підвищення її конкурентних позицій
Keywords: railway industry; competition; state industrial policy; restructuring; reforming; privatization; market position; modernization; залізнична галузь; конкуренція; державна промислова політика; реструктуризація; реформа; приватизація; ринкові позиції; модернізація